Intramuscular Sodium Tetrathionate as an Antidote in a Clinically Relevant Swine Model of Acute Cyanide Toxicity - Hendry-Hofer, Tara B. (Clin Toxicol (Phila), 2019)
BACKGROUND: Cyanide is a metabolic poison used in multiple industries and is a high threat chemical agent. Current antidotes require intravenous administration, limiting their usefulness in a mass casualty scenario. Sodium tetrathionate reacts directly with cyanide yielding thiosulfate and the non-toxic compound thiocyanate. Thiosulfate in turn neutralizes a second molecule of cyanide, thus, per mole, sodium tetrathionate neutralizes two moles of cyanide. Historical studies examined its efficacy as a cyanide antidote, but it has not been evaluated in a clinically relevant, large animal model, nor has it previously been administered by intramuscular injection. OBJECTIVE: The objective of this study is to evaluate the efficacy of intramuscular sodium tetrathionate on survival and clinical outcomes in a large, swine model of severe cyanide toxicity. METHODS: Anesthetized swine were instrumented for continuous monitoring of hemodynamics, then acclimated and breathing spontaneously prior to potassium cyanide infusion (0.17 mg/kg/min). At 6-minutes post apnea (no breaths for 20 seconds), the cyanide infusion was terminated, and animals treated with sodium tetrathionate (~18 mg/kg) or normal saline control. Clinical parameters and laboratory values were evaluated at various time points until death, or termination of the experiment (90 minutes post treatment). RESULTS: Laboratory values, vital signs, and time to apnea were similar in both groups at baseline and treatment. Survival in the sodium tetrathionate treated group was 100% and 17% in controls (P=0.0043). All animals treated with sodium tetrathionate returned to breathing at a mean time of 10.85 minutes after antidote, and all but one control remained apneic through end of the experiment. Animals treated with tetrathionate showed improvement in blood lactate (P≤0.002) starting at 30 minutes post treatment. The average time to death in the control group of 63.3 ± 23.2 min. No systemic or localized adverse effects of intramuscular administration of sodium tetrathionate were observed. CONCLUSION: Sodium tetrathionate significantly improves survival and clinical outcomes in a large, swine model of acute cyanide poisoning.